Lipid Profiles in Lyme Borreliosis: A Potential Role for Apheresis? - Straube, Richard; Voit-Bak, Karin; Gor, A.; Steinmeier, Til; Chrousos, George P.; Boehm, Bernhard Otto; Birkenfeld, Andreas L.; Barbir, Mahmoud; Balanzew, Wladimir; Bornstein, Stefan R. (Hormone and Metabolic Research, 2019)
Dyslipidemia and dyslipoproteinemia are common causes of metabolic and cardiovascular diseases. On the other hand, intracellular bacteria, such as Borrelia burgdorferi, utilize host lipids to survive and disseminate within the host. Recent data suggest that elevated lipids are a contributing factor to the maintenance and severity of Lyme disease and its complications. Here we review and discuss the role of lipids in Borreliosis and report on a pilot trial to examine the potential roles of circulating lipids and lipoproteins in patients with Borrelia infection. In this analysis we assessed the clinical and lipid profiles of 519 patients (319 women, 200 men) with a proven history of Lyme disease, before and after an extracorporeal double membrane filtration. Lipid profiles pre- and post-apheresis were analyzed in conjunction with clinical symptoms and parameters of inflammation. Circulating cholesterol, triglycerides, LDL, LP(a), and other inflammatory lipids were significantly reduced after the apheresis, while symptoms of the disorder and bioindexes of inflammation such as CRP improved. Further studies should be initiated to investigate the possibly causal relation between Lyme disease and circulating lipids and to design appropriate therapeutic strategies.
Keywords: lipidapheresis; borreliosis; inflammation